2017
DOI: 10.20960/nh.950
|View full text |Cite
|
Sign up to set email alerts
|

The effects on nutritional status, bowel habits and tolerance of a high- protein, high-calorie, fiber- and fructo-oligosaccharide-enriched enteral formula: Safety and Effectiveness of Enteral Nutrition in Spanish patients (SENS Study).

Abstract: on behalf of the SENS Working Group. The effects of a high-protein, high-calorie, fiber-and fructooligosaccharide-enriched enteral formula on nutritional status, bowel habits and tolerance: Safety and Effectiveness of Enteral Nutrition in elderly Spanish patients (SENS Study ResumenIntroducción: la nutrición enteral es una intervención efectiva para pacientes desnutridos o en riesgo de sufrir desnutrición. Sin embargo, puede desencadenar complicaciones como intolerancia gastrointestinal, hiperglicemia o síndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…This improvement in nutritional status was also reflected in the evolution of the laboratory parameters, with a statistically significant improvement between baseline and 6 months (Table 5 ). These findings are consistent with a study of 102 patients (56.9% with HEN and 43.1% with hospital EN) treated with a hyperproteic/hypercaloric formula for 8 weeks, which also found improved weight, BMI, albumin and prealbumin parameters [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…This improvement in nutritional status was also reflected in the evolution of the laboratory parameters, with a statistically significant improvement between baseline and 6 months (Table 5 ). These findings are consistent with a study of 102 patients (56.9% with HEN and 43.1% with hospital EN) treated with a hyperproteic/hypercaloric formula for 8 weeks, which also found improved weight, BMI, albumin and prealbumin parameters [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…This improvement in nutritional status was also re ected in the evolution of the laboratory parameters, with a statistically signi cant improvement between baseline and 6 months (Table 5). These ndings are consistent with a study of 102 patients (56.9% with HEN and 43.1% with hospital EN) treated with a hyperproteic/hypercaloric formula for 8 weeks, which also found improved weight, BMI, albumin and prealbumin parameters [20].…”
Section: Discussionsupporting
confidence: 91%
“…The amount of the TRM in the study did not significantly change the GI symptoms in participants. Similarly, Cuesta-Triana reported that eight-week supplementation of fiber-containing formula (1.5 g fiber/100 g ONS) was well-tolerated by the subjects (Cuesta-Triana et al, 2017). In addition, the developed ONS supplementation also did not change the defecation frequency and stool form as evaluated by Bristol Stool Scale.…”
Section: Effect Of Developed Ons Supplementation On Gi Tolerabilitymentioning
confidence: 85%